IL-12 and IL-10 expression synergize to induce the immune-mediated eradication of established colon and mammary tumors and lung metastasis - Lopez, Maria Veronica (2005)
Preclinical studies demonstrated that certain cytokines are potentially useful for the induction of antitumor immune responses. However, their administration in clinical settings was only marginally useful and evoked serious toxicity. In this study, we demonstrate that the combination of autologous inactivated tumor cells expressing IL-12 and IL-10 induced tumor remission in 50-70% of mice harboring large established colon or mammary tumors and spontaneous lung metastases, with the consequent establishment of an antitumor immune memory. Mice treatment with tumor cells expressing IL-12 was only marginally effective, while expression of IL-10 was not effective at all. Administration of the combined immunotherapy stimulated the recruitment of a strong inflammatory infiltrate that correlated with local, increased expression levels of the chemokines MIP-2, MCP-1, IFN-gamma-inducible protein-10, and TCA-3 and the overexpression of IFN-gamma, but not IL-4. The combined immunotherapy was also therapeutically effective on established lung metastases from both colon and mammary tumors. The antitumor effect of the combined immunotherapy was mainly dependent on CD8+ cells although CD4+ T cells also played a role. The production of IFN-gamma and IL-4 by spleen cells and the development of tumor-specific IgG1 and IgG2a Abs indicate that each cytokine stimulated its own Th pathway and that both arms were actively engaged in the antitumor effect. This study provides the first evidence of a synergistic antitumor effect of IL-12 and IL-10 suggesting that a Th1 and a Th2 cytokine can be effectively combined as a novel rational approach for cancer immunotherapy.